Intercomparison of atmospheric dispersion models applied to an urban street canyon of irregular geometry - Dezzutti, Mariana Clara (2018)
The NOx concentrations measured at the sampling site of Cordoba Avenue, Buenos Aires City, characterised by an irregular geometry on both sides of the street, are used to intercompare results of five urban street canyon dispersion models, STREET, OSPM, AEOLIUSF, STREET-BOX and SEUS. Three different wind directions with respect to the street axis are considered, i.e., leeward, windward and parallel. Additionally, two wind speed classes are considered, above and below 2 m s–1. In order to evaluate the models performance, observed and calculated concentrations are compared using different statistical measures, i.e., mean values, bias, mean square error and fractional error. In general, all models estimate better leeward conditions and wind speeds above 2 m s–1, with SEUS providing the overall best result.